2009
DOI: 10.1007/s11661-009-9807-3
|View full text |Cite
|
Sign up to set email alerts
|

Load Partitioning and Strain-Induced Martensite Formation during Tensile Loading of a Metastable Austenitic Stainless Steel

Abstract: In-situ high-energy X-ray diffraction and material modeling are used to investigate the strainrate dependence of the strain-induced martensitic transformation and the stress partitioning between austenite and a¢ martensite in a metastable austenitic stainless steel during tensile loading. Moderate changes of the strain rate alter the strain-induced martensitic transformation, with a significantly lower a¢ martensite fraction observed at fracture for a strain rate of 10 À2 s À1 , as compared to 10 À3 s À1 . Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…A maximum temperature increase is about 35 • C at 0.005 s −1 . The measured data agrees with the calculated and measured results by Haušild et al [6] and Talonen et al [11] and simulated results provided by Hedström et al [5] . Generally, the mechanical energy introduced to the specimen by plastic deformation is almost fully (90%) converted to thermal energy, i.e., adiabatic heating.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…A maximum temperature increase is about 35 • C at 0.005 s −1 . The measured data agrees with the calculated and measured results by Haušild et al [6] and Talonen et al [11] and simulated results provided by Hedström et al [5] . Generally, the mechanical energy introduced to the specimen by plastic deformation is almost fully (90%) converted to thermal energy, i.e., adiabatic heating.…”
Section: Figuresupporting
confidence: 90%
“…Actually, a few experiments and simulations have been implemented to study the martensitic transformation affected by the strain rate during tensile deformation. Hedström et al [5] investigated the strain-rate dependence of the strain-induced martensitic transformation and the stress partitioning between austenite and α martensite in AISI 301 stainless steel during tensile loading. They found that the strain-rate sensitivity of the strain-induced martensitic transformation was high and moderate strain rates of 0.01 s −1 would suppress the α martensite transformation due to adiabatic heating of the tensile specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the work-hardening behavior is due to deformation-induced martensitic transformation (DIMT), which has been the subject of extensive research in commercial steels [1][2][3][4][5]. The austenite (hereinafter referred to as ) stability is critical in order to tailor the mechanical properties of these alloys, and it can be correlated to three fundamental factors: i) chemical driving force (-ΔG chem fcc→bcc/hcp ), ii) mechanical driving force (-ΔG mech fcc→bcc/hcp ), and iii) strain-induced generation of potent nucleation sites.…”
Section: Introductionmentioning
confidence: 99%
“…In an annealed soft state, the metastable austenitic stainless steels (MASSs) are fully austenitic (γ); they can be strengthened by grain refinement [17] and by its transformation into martensite (α') under the application of stress/strain [18,19]. The increase of the work-hardening of the steel as a consequence of the martensitic transformation results in enhanced strength and formability, which makes MASSs good candidates for multi-stage processes [20][21][22]. …”
Section: Microstructure Of the Pointed Zone By The Rspmmentioning
confidence: 99%